Enhancing Sharia Insurance Development in Indonesia: The Role of Fintech and Product Innovation - Kusuma, Mitra Dewi; Daulay, Aqwa Naser; Nasution, Juliana (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
This research uses quantitative methods and secondary data to investigate the impact of Financial Technology (Fintech) and product innovation on developing the Sharia insurance industry in Indonesia. The study uses multiple linear regression analysis to explore the relationship between independent variables (Fintech usage and product innovation) and the dependent variable (Sharia insurance development) for 2014-2023. Secondary data, sourced from reliable institutions such as financial reports and the Financial Services Authority (OJK), is analyzed to uncover these relationships. The findings reveal a significant positive correlation between both Fintech and product innovation and the overall development of Sharia insurance. Although product innovation alone does not show a significant statistical impact, it significantly affects Sharia insurance development when combined with Fintech. However, the influence of these variables is likely moderated by other factors such as regulatory changes, public perception, and economic conditions. This study enriches the existing literature on fintech and product innovation by providing empirical evidence of their effects on the growth of Sharia insurance in Indonesia.